Estudo da secagem de café arábica (Coffea arabica L.) despolpado em secador roto-aerado - Andrade, Paulo Sérgio de (2023)
Arabica coffee post-harvest processing is usually done by mechanical or terrace drying, aiming to reduce the bean moisture content to a safe level. The techniques used have as characteristics a long drying time and undesirable material degradation. So, it is timely to investigate and propose an alternative technique that reduces processing time and maintains product quality. Thus, this study aimed to improve the drying operation of pulped arabica coffee, without parchment and previously dried on a terrace, through the: characterization of the raw material, followed by the evaluation of the drying performance, modeling of the simultaneous heat and mass transfer between the coffee and the air in a non-conventional rotary dryer, the correlation between physicochemical attributes and coffee quality and, finally, determination of optimal operating conditions to balance the drying performance and product quality. The material geometric parameters were obtained through image analysis by particle flow. The image analysis also made it possible to determine several aspects related to the particle morphology, including sphericity and aspect ratio. The thermal decomposition of pulped coffee was investigated by thermogravimetric analysis (TGA). Drying experiments were performed at distinct levels of temperature (Tf) and air velocity (vf), as well as feed flow rate (Ws). After reaching a steady state, samples were collected for drying performance, modeling, and coffee quality verification. The drying operations were executed according to a Central Composite Design (CCD) with 16 experiments. A two-phase model with an appropriate set of constitutive equations was used to describe the drying process. The equations system was solved numerically using the collocation technique. The coffee quality was evaluated by determining moisture, water activity, pH, titratable acidity (TA), and sugar and organic acid contents. The average residence time of the material in the dryer varied from 14.60 to 27.47 min, which is shorter than in other types of dryers used for coffee processing, representing a reduction of up to approximately 88% in drying time. The drying rates in the roto-aerated dryer varied from 0.09 to 0.24 p.p./min and were much higher than those obtained for coffee in other drying techniques. In general, the higher reduction in coffee moisture was associated with conditions that led to a higher drying rate and heating of the coffee. The simulated results showed good agreement with the data. The average difference between experimental and simulated results was 2.39 % for coffee moisture and 0.89 % for coffee temperature. Even though the coffee temperature exceeded 40 or 45 °C during some experiments, the exposure time was so low that it did not decrease the quality of the bean, regarding titratable acidity and its balance with sweetness (sucrose/TA). Besides having a better drying performance than other dryers, the roto-aerated also contributed to the preservation of coffee quality regarding total acidity, water activity, sugars, and organic acids. The desirability function resulted in optimal levels of operational variables of vf = 2.7 m/s, Tf = 81.8 °C, and Ws = 40 g/min.